CHILDREN'S BEHAVIOR IN CONSUMING SNACKS AT SDN 01 TAMAN MADIUN CITY - Intan Ariani; Zaenal Abidin; Riska Ratnawati (AKADEMI KEBIDANAN HARAPAN MULYA PONOROGO, 2023)
Snack food (FAO) is food and drink served and sold by street vendors to be consumed or enjoyed directly on the street or in other public places without further processing or preparation. In this study, researchers used qualitative research and the research used in this study was a phenomenological approach that aims to understand the essence of a phenomenon in children's behavior in choosing snacks at school. The informants of this research were 10 students/I grade VI SDN 01 Taman Kota Madiun. The results of the research carried out, obtained statements that indicate there is still a lack of knowledge of informants regarding healthy snacks, the attitude of children who buy various types of snacks at school, children's pocket money above Rp. 5000-, so that children freely choose snacks at school, habits different breakfasts, as well as the role of peers who play a role in children's behavior in choosing snacks at school. The conclusion in this study about children's behavior in choosing snacks at school is that not all informants behave well when choosing snacks, most of them buy snacks because they are hungry regardless of the content in the food. From the results of this study, suggestions are given to students in order to understand which snacks are good for consumption and not to snack randomly.